Association of lipid profile with severity of hepatitis B virus related chronic liver disease in adult (Bangladesh Medical Journal Khulna, 2022)
Background: Chronic liver disease (CLD) is a major health problem and contributes to a common cause of hepatocellular carcinoma, disability and death worldwide. Hepatitis B virus (HBV) is the leading cause of CLD in our country. Abnormal lipid profile is expected in those with severe liver dysfunction.Objective: The objective of the study was to determine the alteration of lipid profile (total cholesterol, triglyceride, LDL-C and HDL-C) in HBV positive adult CLD patients and to correlate with severity of liver damage.Methods: This case control study was conducted for one year between January 2018 to December 2018. One hundred and three patients, >18 years old, admitted with HBV positive CLD in Dhaka Medical College Hospital were recorded as case and 103 age and sex matched, healthy population, were recorded as control. A standard case record form including demographics, histories, clinical examinations and different investigations were completed for each group. Then lipid profile values of cases were compared to controls and different Child-Pugh and MELD scores, were used to see severity of liver damage in CLD patients.Results: In patients with HBV positive adult CLD, there were a significant decrease in serum total cholesterol. LDL-C and HDL-C levels compared to the control group (mean 131.4 vs 179.3, 72.5 vs 109.6, and 31.0 vs 40.4 mg/dl, respectively; p